2011
DOI: 10.1074/jbc.m110.203000
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Mitochondrial Carrier SLC25A25 (ATP-Mg2+/Pi Transporter) Reduces Physical Endurance and Metabolic Efficiency in Mice

Abstract: An ATP-Mg 2؉/ P i inner mitochondrial membrane solute transporter (SLC25A25), which is induced during adaptation to cold stress in the skeletal muscle of mice with defective UCP1/ brown adipose tissue thermogenesis, has been evaluated for its role in metabolic efficiency. SLC25A25 is thought to control ATP homeostasis by functioning as a Ca 2؉ -regulated shuttle of ATP-Mg 2؉ and P i across the inner mitochondrial membrane. Mice with an inactivated Slc25a25 gene have reduced metabolic efficiency as evidenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 44 publications
6
77
0
Order By: Relevance
“…Notably, previous studies in rats housed at thermoneutrality failed to find any substantial contribution of BAT activity to diet-induced thermogenesis 58 . Moreover, Anunciado-Koza et al 55 did not observe changes in adiposity in their studies of Ucp1 knockout mice when the mice were housed under varying temperature conditions. In addition, increases in BAT or Ucp1 activity in response to high-fat feeding are not consistently observed 59 .…”
Section: Regulation Of Brown and Beige Adipocytes By Prdm16mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, previous studies in rats housed at thermoneutrality failed to find any substantial contribution of BAT activity to diet-induced thermogenesis 58 . Moreover, Anunciado-Koza et al 55 did not observe changes in adiposity in their studies of Ucp1 knockout mice when the mice were housed under varying temperature conditions. In addition, increases in BAT or Ucp1 activity in response to high-fat feeding are not consistently observed 59 .…”
Section: Regulation Of Brown and Beige Adipocytes By Prdm16mentioning
confidence: 99%
“…At room temperature (20-22 °C), mice are cold and must therefore expend extra energy to defend their body temperature. Ucp1-deficient mice, which cannot use BAT, activate alternative thermogenic mechanisms 55,56 . This is thought to conceal the effect of brown fat and Ucp1 on energy balance.…”
Section: Regulation Of Brown and Beige Adipocytes By Prdm16mentioning
confidence: 99%
“…Although BAT is unequivocally a dominant thermogenic mechanism in rodents, several studies have suggested other mechanisms of heat production. Indeed, published studies on cold-adapted UCP1-KO mice have implicated that Ca 2ϩ cycling in skeletal muscle, thermogenesis from white adipose tissue (UCP1-independent), and substrate cycling in skeletal muscle could be recruited to produce heat, but none of these mechanisms were found to be dominant (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…These approaches stimulate facultative thermogenic responses that uncouple substrate oxidation from ATP synthesis, dissipate the mitochondrial proton gradient, and release chemical energy as heat. Other possibilities to enhance energy expenditure by decreasing the metabolic efficiency of obligatory cellular processes remain largely unexplored (Alekseev et al 2010;Anunciado-Koza et al 2011;Oie et al 2014).…”
mentioning
confidence: 99%